Case Report: Sequential Combination Targeted Therapy With Type I and II MET Inhibitors in a Metastatic EGFR-Mutated, MET-Amplified NSCLC Patient With Acquired MET Y1230H Mutation - Cai, Boning; Li, Xiaomo; Huang, Xiang; Ma, Tonghui; Qu, Baolin; Yu, Wei; Yang, Wei; Zhang, Pei; Chen, Jing; Liu, Fang (Frontiers in Oncology, 2021)
Epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) are the standard of care for advanced non-small-cell lung cancer (NSCLC) patients harboring sensitizing EGFR mutations. However, most patients will eventually develop resistance to EGFR-targeted therapy. Increasing knowledge of de novo and acquired resistance mechanisms allows oncologists to develop mechanism-based therapies to overcome therapeutic resistance. For instance, in EGFR-mutant NSCLC patients with EGFR TKI resistance mediated by MET amplification, the combination therapy of EGFR and MET TKIs has shown promising results in early clinical trials. However, acquired on-target resistance to MET inhibitors forms a formidable challenge to this approach. Here we describe an EGFR-mutant, MET-amplified NSCLC patient who was resistant to first-line erlotinib treatment but responded to the combination targeted therapy of gefitinib plus type 1 MET inhibitor crizotinib after the failure of chemotherapy. After disease progression, molecular testing of the biopsy revealed an acquired MET Y1230H mutation and PD-L1 TPS score of 75%. The patient received a combination treatment regime consisting of gefitinib, type 2 MET inhibitor cabozantinib, and PD-1 antibody pembrolizumab with a prolonged response. Our work suggests that the combination of EGFR TKI with either crizotinib or cabozantinib may serve as the backbone for effective therapeutic options in advanced EGFR-mutant, MET-amplified NSCLC patients.